Neuroprotective effects of bavachalcone in a mouse model of Parkinson’s disease: linking the gut-brain axis and systemic metabolism - Shi, Shuai; Bian, Xiaohan; Li, Mengyun; Zhang, Xiaobing; Huang, Wenji; Shao, Xian; Lu, Tiantian; Yu, Xuebin (Frontiers in Neuroscience, 2025)
BackgroundParkinson’s disease (PD) is a progressive neurodegenerative disorder characterized by motor dysfunction and dopaminergic neuronal loss. Emerging evidence suggests that gut microbiota dysbiosis and systemic metabolic disturbances contribute to the pathogenesis of PD. This study aimed to investigate the neuroprotective effects of bavachalcone, a prenylated chalcone isolated from Psoralea corylifolia, in an MPTP-induced mouse model of PD, with a particular focus on its effects on motor function, inflammation, gut microbiota, and serum metabolism.MethodsMale C57BL/6 mice were divided into Control, MPTP, Bavac-L (low-dose bavachalcone), and Bavac-H (high-dose bavachalcone) groups. Bavachalcone was administered by gavage, followed by MPTP injection to induce PD. Behavioral assessments (open field test, pole test, and rotarod test), western blotting, immunohistochemistry, immunofluorescence, 16S rDNA sequencing of fecal microbiota, and untargeted metabolomics of serum were performed to evaluate the effects of bavachalcone.ResultsBavachalcone significantly alleviated MPTP-induced motor impairment, preserved dopaminergic neurons in the substantia nigra and striatum, and reduced systemic inflammation and glial activation. Gut microbiota analysis showed that bavachalcone improved microbial richness and diversity, enriched beneficial genera, such as Allobaculum, and suppressed harmful taxa, such as Ligilactobacillus and Helicobacter. Metabolomic profiling revealed that bavachalcone modulated pathways, including pyruvate metabolism, folate biosynthesis, and phenylalanine metabolism.ConclusionBavachalcone exerts neuroprotective effects in mice with PD by improving motor function, preserving dopaminergic neurons, reducing inflammation, modulating gut microbiota composition, and remodeling systemic metabolism. These findings highlight bavachalcone as a promising therapeutic candidate for PD.